ВІЙСЬКОВО-ПАТРІОТИЧНЕ ВИХОВАННЯ МОЛОДІ В КРАЇНАХ СТАЛОЇ ДЕМОКРАТІЇ: ЗАВДАННЯ ТА ОСОБЛИВОСТІ - Бондаренко, Олександр (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті висвітлено й проаналізовано досвід військово-патріотичного виховання молоді в таких країнах, як США, Німеччина, Франція, Великобританія, Японія; визначені зміст, мета, завдання і особливості військово-патріотичного виховання молоді в сучасних країнах сталої демократії. З’ясовано, що фундамент процесу формування та становлення соціальних властивостей та якостей особистості започатковується в молодому віці. Встановлено, що таким фундаментом може виступати військове училище (кадетський корпус), як ключова ланка в структурі військової освіти. В статье освещен и проанализирован опыт военно-патриотического воспитания молодежи в таких странах, как США, Германия, Франция, Великобритания, Япония; определены содержание, цели, задачи и особенности военно-патриотического воспитания молодежи в современных странах устоявшейся демократии. Выяснено, что фундамент процесса формирования и становления социальных свойств и качеств личности создается в молодом возрасте. Установлено, что таким фундаментом может выступать военное училище (кадетский корпус), как ключевое звено в структуре военного образования. The article highlights and analyzes the experience of military-patriotic education of youth in the system of education in the USA, Germany, France, Great Britain, Japan; defined content, goals, tasks and features of the militarypatriotic education of youth in most developed countries with a stable democracies. It was found that the basis of the formation of social properties and qualities of the personality is formed in a young age. A Military School (Cadet Corps) can be considered as a foundation and a key element in the structure of the military education. Therefore, the average special military educational institutions are considered as a key social institution of formation of identity of the future officer. The article shows that under current conditions, we can highlight the following goals among the tasks of the military-patriotic education in the countries of stable democracies: education of the harmonious manifestation of the youth patriotism, tolerance, humanity, dignity and inner freedom, discipline and professional competence. Based on the experience of foreign theory and practice, it should be noted that modern patriotism and military-patriotic education of youth are characterized by: devotion to his country (place of origin or place of living), willingness to bear great sacrifices (and even sacrifice their lives) willingness to act for the common welfare and solidarity with the other members of the national or regional community, respect for the law, in good faith and honest work, in interest in history, language, in study of national culture, rejection of the speculation with the theory of the enemy.